Targeted anti-angiogenesis therapy for advanced osteosarcoma - Zhang, Qiao; Xia, Yuxuan; Wang, LiYuan; Wang, Yang (Frontiers in Oncology, 2024)
To date, despite extensive research, the prognosis of advanced osteosarcoma has not improved significantly. Thus, patients experience a reduced survival rate, suggesting that a reevaluation of current treatment strategies is required. Recently, in addition to routine surgery, chemotherapy and radiotherapy, researchers have explored more effective and safer treatments, including targeted therapy, immunotherapy, anti-angiogenesis therapy, metabolic targets therapy, and nanomedicine therapy. The tumorigenesis and development of osteosarcoma is closely related to angiogenesis. Thus, anti-angiogenesis therapy is crucial to treat osteosarcoma; however, recent clinical trials found that it has insufficient efficacy. To solve this problem, the causes of treatment failure and improve treatment strategies should be investigated. This review focuses on summarizing the pathophysiological mechanisms of angiogenesis in osteosarcoma and recent advances in anti-angiogenesis treatment of osteosarcoma. We also discuss some clinical studies, with the aim of providing new ideas to improve treatment strategies for osteosarcoma and the prognosis of patients.